2011
DOI: 10.1111/j.1600-0471.2010.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Monks, dinars and date palms: hagiographical production and the expansion of monastic institutions in the early Islamic Persian Gulf

Abstract: Der Weg in die Wüste war der radikalste dichterische Akt… Peter Sloterdijk, Weltfremdheit Recent archaeological studies have documented an expansion of monastic institutions in the Persian Gulf after the Islamic conquest, between the middle of the seventh and the end of the eighth centuries. Although the literary sources have often been invoked to support an earlier dating for the diffusion of coenobitic monasticism in the region, our principal source for the phenomenonthe History of Mar Yonan, hitherto misdat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…These are also apparent in the name of the neighbouring village to the west, Al‐Dair, or Dayr, meaning ‘monastery’ or ‘cloister’ in Aramaic (Potts, 1990: 12). Moreover, Muharraq, like Sir Bani Yas and Kharg, would accord with Payne’s (2011: 99) observation that coenobitic monasticism in the Arabian Gulf emerged ‘on islands whose topography invited a re‐imagination of the deserts of Egypt’. A Christian identity for the occupants of Building 1 is suggested by the cross‐painted yellow glaze family (YGF)/Coptic glazed ware/Hijazi ware sherd, limestone block engraved with a possible Cross, decorated stucco, glass vessel forms and chronology.…”
Section: Discussion: Samahij and The Implications For Christianity Is...mentioning
confidence: 84%
See 1 more Smart Citation
“…These are also apparent in the name of the neighbouring village to the west, Al‐Dair, or Dayr, meaning ‘monastery’ or ‘cloister’ in Aramaic (Potts, 1990: 12). Moreover, Muharraq, like Sir Bani Yas and Kharg, would accord with Payne’s (2011: 99) observation that coenobitic monasticism in the Arabian Gulf emerged ‘on islands whose topography invited a re‐imagination of the deserts of Egypt’. A Christian identity for the occupants of Building 1 is suggested by the cross‐painted yellow glaze family (YGF)/Coptic glazed ware/Hijazi ware sherd, limestone block engraved with a possible Cross, decorated stucco, glass vessel forms and chronology.…”
Section: Discussion: Samahij and The Implications For Christianity Is...mentioning
confidence: 84%
“…The relevant Syriac and less comprehensive Arabic historical sources have been extensively explored (Beaucamp & Robin, 1983; Potts, 1990; Langfeldt, 1994; Bin Seray, 1996, 1997; Payne, 2011; Carter 2013), and it has been suggested that the Bishopric of Mašmahig can be linked with the village of Samahij in north‐east Muharraq Island, Bahrain (Potts, 1990: 150; Langfeldt, 1994: 54; Bin Seray, 1997: 217; Carter, 2008: 101). However, archaeological evidence for a Christian presence in Samahij, or elsewhere in Bahrain, was lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the seemingly growing gap in the conclusions suggested by the two bodies of material, I hope to have demonstrated that it is possible to construct models which seem to allow for a combination of both. In this sense, this article can sit together with another recent publication which demonstrated that the—at first—seemingly divergent literary and archaeological evidence for the presence of Christian monasticism on the Arabian side of the Gulf can in fact be reconciled, through a careful and contextualised reading of the narrative sources, to present a coherent picture (Payne, ). We have seen that although Ps.‐ʿAwtabī's account of relationships between the Sasanian rulers and local Omani tribes offers interesting information about the way the pre‐Islamic period in south‐east Arabia was remembered in the fourth/tenth century, it is not very clear how much of the information it provides presents an accurate picture of the situation in the sixth and early seventh centuries.…”
Section: Literary and Archaeological Evidence For Late Sasanian Arabiamentioning
confidence: 81%
“…This may indicate that previous itineraries that bypassed the Romano-Sāsānian border via ʿAqaba and Gaza or Egypt began, during early Islam, to take the shortest route, leading in particular to the rapid isolation of Yemen and Ḥijāz, and changing the image that chroniclers of the ʿAbbāsid period had of the original Arabian sub-continent. Evidence on the blooming of maritime trade in Baṣra during the early Islamic period can be found in Syriac sources on the gulf monastic economy (Payne 2011), in witness statements of the composite Middle Eastern diasporas settled on the Western Indian Shore (see on later testimonies Lambourn, Veluthat and Tomber 2020) and in testimonies of the rise of Indianised states all around the Bay of Bengal.5 Thus, the fierceness of the outbreaks that hit the city suggests that its strategic commercial position accelerated the spread of the bacillus, in part due to the opening of a direct connection from the Mediterranean to the Indian Ocean.…”
Section: 3mentioning
confidence: 99%